Pemberian Komunikasi, Informasi Dan Edukasi (KIE) Adaptasi Psikologi Post Partum Sebagai Upaya Pencegahan Postpartum Blues Pada Ibu Nifas Di UPT Puskesmas Kec. Alas Barat - Fitri Setianingsih; Yunita Lestari; Galuh Permatasari; Nurlaila Agustikawati (Institut Teknologi dan Bisnis Semarang, 2024)
Psychological adaptation in postpartum mothers begins when the mother enters the period after giving birth, such as the mother starting to care for and take care of her baby, this is a new role and responsibility for every woman after giving birth. These new roles and responsibilities often make mothers feel insecure and stressed. Which is based on the mother's feelings of sadness and despair because she has not been able to care for the baby well. This is known as baby blues or postpartum blues. Baby blues has mild effects that can occur on the first day after postpartum, days 3-5 tend to get worse and last within 14 days or 2 weeks postpartum. With support from the extended family, partner and closest friends, the mother will feel safer and more comfortable, thereby improving the level of health of the mother and child, both physically and spiritually. In this case, IEC is carried out regarding postpartum psychological changes for mothers and families as an effort to prevent and overcome the incidence of post partum blues in mothers. From this community service activity, it was found that mothers, husbands and families understand the post partum psychological adaptations that can occur in postpartum mothers and the family will try to continue to help the mother in caring for her baby, comfort the mother and also always provide positive support so that the mother is able to and confident in caring for the baby so that the baby and mother are physically and mentally healthy.